Exercise training in COPD with exercise-induced desaturation does improve exercise capacity, irrespective of whether supplemental oxygen or air is provided during training. Issue 5 (14th November 2019) - Alison, Jennifer A.; McKeough, Zoe J.; Leung, Regina W.M.; Holland, Anne E.; Hill, Kylie; Morris, Norman R.; Jenkins, Sue; Spencer, Lissa M.; Hill, Catherine J.; Lee, Annemarie L.; Seale, Helen; Cecins, Nola; et al.
We thank D. Langer and R. Gosselink for their correspondence about our study [1 ]. They raise some interesting points, mainly related to training intensity. In people with COPD who desaturate during exercise, similar improvements in exercise capacity and health-related quality of life can be achieved with exercise training, irrespective of whether supplemental oxygen or air is provided during training http://bit.ly/2kKGGvi